Synthesis and Characterization of Complexes of Non-transition Elements. - RAMAPPA, P.G.; NAGARAJAPPA., K.C. (Asian Journal of Chemistry, 2010)
New complexes of bismuth and tin prepared from promethazine hydrochloride (PH), prochlorperazine dimaleate (PCPM) and isopropamide hydrochloride (IPPH) have been characterized by conductivity, spectroscopic and elemental analyses. The conductometric measurements in DMF, DMSO and acetonitrile solution indicate their non-electrolyte nature. TGA data show that Bi(III) complexes are thermally stable up to 135ºC whereas Sn(II) complexes are thermally stable upto 230ºC. The ligands behave as bidentate in all these complexes. The Bi(III) complexes are assigned octahedral structure while Sn(II) complexes square-planar geometry.